(untitled) (Repertorio Científico, 2020)
Angiostrongylus costaricensis is a nematode of medical importance in America. In the present study, a complete and precise ultrastructural description of A. costaricensis was made at each of its stages of development. A minimum of 20 specimens per evolutionary stage were studied which were processed for scanning microscopy and were observed and photographed at magnifications from 25 to 3000X.